Developing Detailed Rubrics for Assessing Critique Writing - Diab, Rula (2015)
The purpose of this study was to develop specific rubrics for assessing critiques in English 202, an English as a foreign language course at the Lebanese American University to explore the effectiveness of these rubrics on students' writing and to investigate students' attitudes and reactions to the use of these rubrics. After development of the rubrics, students wrote an in-class critique of an article, using the rubrics as a guide. Based on teachers' comments and grades on the rubrics, students revised and wrote the second draft. Students were then administered an anonymous online survey asking them for feedback on the use of rubrics. A t-test comparing students' grades on the first and second drafts revealed a significant difference, suggesting that use of the rubrics helped students effectively revise their drafts. The survey results support this hypothesis because students revealed positive attitudes and reactions. Based on the findings, we recommend that consistent use of well-developed rubrics can enhance outcomes for English learners enrolled in writing courses.The purpose of this study was to develop specific rubrics for assessing critiques in English 202, an English as a foreign language course at the Lebanese American University to explore the effectiveness of these rubrics on students' writing and to investigate students' attitudes and reactions to the use of these rubrics. After development of the rubrics, students wrote an in-class critique of an article, using the rubrics as a guide. Based on teachers' comments and grades on the rubrics, students revised and wrote the second draft. Students were then administered an anonymous online survey asking them for feedback on the use of rubrics. A t-test comparing students' grades on the first and second drafts revealed a significant difference, suggesting that use of the rubrics helped students effectively revise their drafts. The survey results support this hypothesis because students revealed positive attitudes and reactions. Based on the findings, we recommend that consistent use of well-developed rubrics can enhance outcomes for English learners enrolled in writing courses.